PROGNOSTICALLY SIGNIFICANT PARAMETERS FOR DETERMINING THE LIKELIHOOD OF PROGRESSION OF SPINAL DEFORMITY IN IDIOPATHIC SCOLIOSIS IN CHILDREN AND ADOLESCENTS BASED ON CORRELATION ANALYSIS - Umarhodzhaev, F.R.; Iskandarov, M.M. (Toshkent tibbiyot akademiyasi axborotnomasi, 2020)
Objective: Selection of prognostically significant parameters for determining the likelihood of progression of spinal deformity in idiopathic scoliosis in children and adolescents. Material and methods: To make a forecast, we used a map of prognostic signs. Fourteen relatively simple clinical and instrumental signs were identified, their prognostic value and gradation were studied, the informative value of the main prognostic signs (the relationship of the sign with the prognosis of the disease) was determined. Currently, several factors have been identified to recognize the progression of scoliosis. Results: The developed methodology for predicting the dynamics of scoliosis in children allows us to differentially determine the tactics of conservative and surgical treatment, and solves the issues of medical examination. The information content of reliable signs of prediction makes it possible to evaluate the effectiveness of the treatment of scoliosis. Conclusions: Prognostic signs, both clinical and radiological, allow to a certain extent to predict the course of scoliosis in specific patients and make a reliable forecast.